Microbial Analysis of Biomedical Wastes from Selected Health Facilities in Parts of Edo South and its Public Health Implication - Rachael Ngozi Osagie; Aidevbo Aibuovbo Eyaufe; Faith Ireye (International Journal of Public Health Science (IJPHS), 2016)
This study, aimed at the microbial analysis of biomedical waste (BMW) was carried out using 100 samples of 10 different BMW collected in duplicates from 5 busy primary healthcare centers (PHCs).The research findings showed a high prevalence of E.coli (39%) and S.aureus (32%) which were both statistically significant at P≤0.05, while the least isolated organisms were K. pnuemoniae (10%) and B. subtilis (4%) and were statistically not significant at P≥0.05. Samples from dressings and beddings were found to contain the highest microbial loadof 25 and 13 respectively while the least number of isolates were from expired cytotoxic drugs (2) and lancets (1).The biochemical tests showed the presence of Gram positive and negative organisms with record of both aerobic and anaerobic isolates from the BMW. The investigation revealed that BMW contains mixed bacterial community with some being pathogenic and pose a public health hazard to both health workers and other community members, therefore adequate treatment measures should be given to all BMW before disposal.